Implementing an Effective Cost Control Strategy at Stations: Case Study of PIA - Syed Sartaj Qasim; Tauseef Qureshi (Institute of Business Management, 2018)
This case study describes the process of developing and implementing a strategy to control costs and reduce losses on account of frauds, accounting errors, wrong payments, etc., at the worldwide outstations of an airline where traditional oversight methods had fallen short of management expectations. By identifying the systemic weaknesses in various areas of station disbursement accounting arising out of lack of training, non-availability of important corporate policies and management directives and lack of standard procedures for preparing and dispatching disbursement reports to head office, a comprehensive Stations Disbursement Manual was developed to train and empower the managers at stations to control and release payments in a responsible manner.